New insights in structural characterization of transparent ZnS ceramics hot-pressed from nanocrystalline powders synthesized by combustion method. Issue 10 (August 2019) - Durand, Guillaume R.; Hakmeh, Noha; Dorcet, Vincent; Demange, Valérie; Cheviré, François; Merdrignac-Conanec, Odile
Abstract: Zinc sulfide transparent ceramics have been fabricated by hot pressing (HP) powders prepared by a newly developed combustion method. Chemical, structural and microstructural properties of powders and ceramics were characterized using different experimental techniques (XRD, SEM-EDS, laser granulometry, TEM, BET, FT-IR spectroscopy). ZnS powders were densified to full density by HP under vacuum atmosphere. The ceramics exhibit highly dense microstructure with mean grain size of 1 μm. TEM characterization identified, both in powders and ceramics, twins and simple stacking faults due to the aperiodic distribution of hexagonal domains. With optical transmission of the theoretical level (∼75%), without absorption band (at 6 μm) and with negligible optical loss, in the 4–12 μm region, the ceramics exhibit better optical performances than standard grade CVD ZnS, and unprecedented performances for hot-pressed ZnS.